No pork, no lard, no trust? examining halal literacy, brand trust, and religiosity in Indonesia's halal market - Santi Retno Sari; Hendryadi Hendryadi; Amelia Oktrivina; Eddy Setyanto; Swarmilah Hariani (LPMP Imperium, 2025)
Purpose – This study examines the mediating role of brand trust in the relationship between halal certified literacy and purchase intention, and the moderating role of religiosity among university students in Jakarta. Methodology – A quantitative causal-explanatory design was used. Data were collected from 101 university students across four universities in Jakarta. Hypotheses were tested using PLS-SEM with bootstrapping. Findings – Halal certified literacy positively affects both brand trust and purchase intention. Brand trust also positively influences purchase intention and fully mediates the relationship between halal literacy and purchase intention. Religiosity significantly moderates the relationship between halal literacy and brand trust, and strengthens the indirect effect of halal literacy on purchase intention through brand trust. All six hypotheses were accepted. Originality/Value – This study extends the Theory of Planned Behavior by positioning halal certified literacy as an antecedent of brand trust and introducing religiosity as a boundary condition that amplifies the effect of halal literacy on trust. It also provides empirical evidence from an under-researched context: Muslim university students in Indonesia who face informal halal claims like